Software-protótipo para o acompanhamento do crescimento e desenvolvimento infantil a partir da classificação internacional das práticas de enfermagem (CIPE®) - Dantas, Cilene Nunes (2016)
This study aimed to develop a software (prototype) for nursing consultation applied to the monitoring of child growth and development in Primary Health Care, whose specific objectives were to build and validate the content of a nursing history instrument for the first consultation and Applied to the monitoring of child growth and development, based on the Basic Human Needs Theory and the International Classification for Nursing Practices; Propose a software (prototype) for the nursing consultation applied to the monitoring of child growth and development. This is a methodological study for the elaboration of the nursing consultation instrument that consisted of five phases: literature review; Structuring of the instruments for validation of EC content for the monitoring of children's CD; Selection of judges for participation in the study; Validation of Nursing History content: Delphi Technique; And development of the Telenfermagem environment (software-prototype) for the follow-up of the children's CD. The research followed the ethical precepts that govern the scientific research with human beings of the National Health Council, approved by the Committee of Ethics and Research, through Opinion No 925.408, of 12/18/2014, under the number CAAE 39640914.8.0000.5537 . The data analysis was performed by simple descriptive statistics, using absolute and relative frequencies, mean, standard deviation, binomial test and IVC. The results were presented in three manuscripts: 1. Nursing consultation to monitor child growth and development in Primary Health Care: integrative review; 2. Validation of a nursing history instrument for monitoring child growth and development; 3. Software-prototype for the follow-up of children's growth and development in Primary Health Care. The first article is related to the findings to characterize the child's consultation, which revealed gaps in the monitoring of children's CD due to limitations related to Theoretical and / or practical knowledge of the nurse in PHC. The second article reveals the validation of content of the instruments for the first and subsequent consultation applied to the child. It refers to the use of the Delphi 1 stage, in which eight judges evaluated the nursing history instruments of Delphi 2 and 3, 6 stages. The nursing history for the first and subsequent consultations were evaluated by the judges according to the criterion of agreement. The instruments that obtained a consensus of 80% among experts were considered valid in their content. Article 3 is related to software, developed on web platform and presents the previously established requirements that are related to the system, resulting in activities that are accessible to the users (administrator and nurse user) registered in the system. Thus, the conclusions point out that the elaborated and validated nursing and software tools have potentialities and limitations, could guide the practice of the nurse in the Family Health Strategy, provide more effective communication, nurse empowerment and autonomy in Primary Care the health.